Wells syndrome - Manish Bansal; Tulika Rai; Shyam S Pandey (Wolters Kluwer Medknow Publications, 2012)
Wells syndrome or eosinophilic cellulitis is characterized clinically by an acute dermatitis resembling cellulitis and histopathologically by dermal eosinophilic infiltration. Various morphological presentations have been described. We report a 32-year-old female with recurrent, erythematous plaques on left forearm of 8 months duration, associated with mild itching that resolved leaving mild hyperpigmentation.